APPLICATION OF THE PRINCIPLES OF THE CIRCULAR ECONOMY IN CONVENTIONAL AGRICULTURE. CASE STUDY - PESTICIDE WASTE RECYCLING - Alina MARCUȚĂ; Cristiana TINDECHE; Valentina TUDOR; Cosmina CARBARĂU (SMEDESCU); Dragoș SMEDESCU; Liviu MARCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Conventional farming systems have been an alternative given that global population growth has been accompanied by an increase in food needs, and areas for production have not been able to keep pace with growth. But the practice of conventional agriculture is the one that, along with other ways of aggressive exploitation of natural resources, economic development, has contributed to environmental degradation and resource depletion. Under these conditions, alternative solutions were sought both to reduce the pressure on the environment, but also to obtain healthier foods that would thus contribute to improving human health. Organic farming, sustainable agriculture, uses principles that have been applied for a long time, but with the advent of the concept of circular economy, as a way to reduce pollution and improve the health of the planet, have been sought solutions for its application in agriculture conventional. In this paper we aim to analyze the current situation of the use of pesticides in agriculture, as an important source of pollution, as well as the possibilities of implementing the principles of circularity in their use, given their high degree of toxicity. The working methodology involved the collection of existing data in national databases, as well as in international ones on the quantities of pesticides sold, the quantities of packaging resulting from their use, but also the possibilities of collection and recycling, as a way of applying recircularity. Based on the processed, analyzed and interpreted data, conclusions were formulated that could be the basis for establishing measures regarding the implementation of efficient circularity systems in agriculture.